A Composite Corrosion Inhibitor of MgAl Layered Double Hydroxides Co-Intercalated with Hydroxide and Organic Anions for Carbon Steel in Simulated Carbonated Concrete Pore Solutions. Issue 11 (1st January 2019) - Cao, Yanhui; Zheng, Dajiang; Dong, Shigang; Zhang, Fan; Lin, Jinyan; Wang, Cheng; Lin, Changjian
Abstract : Corrosion of steel in concrete has resulted in shorter service life of concrete constructions and it may also cause serious safety accident. Chloride attack and carbonation of the concrete are two of the most crucial trigger factors for the initiation of corrosion. In order to protect the reinforced steel in concrete from corrosion, in this work, a composite inhibitor of layered double hydroxides (LDHs) intercalated with organic phthalates (PTL) and hydroxide ions (MgAl-LDHs-OH-PTL) were synthesized by calcination-reconstruction methods in ambient atmosphere. The structure, composition and morphology of the prepared MgAl-LDHs-OH-PTL were obtained by X-ray diffraction, Fourier transform infrared spectroscopy and Scanning Electron Microscopy, respectively. The electrochemical measurements indicated that the inhibition efficiency of MgAl-LDHs-OH-PTL for carbon steel in the simulated carbonated concrete pore (SCCP) solutions reached more than 90% when its concentration was 20 g/L. It was found that the MgAl-LDHs-OH-PTL possessed multifunctional protection roles for the carbon steel in concrete, which mainly included decrease of aggressive Cl − ions, increase of the pH of SCCP solutions and release of PTL anions to the solution gradually. The work indicated the promising potential of LDHs compounds as effective multifunctional inhibitors in the field of corrosion protection of reinforced concrete.